2015
DOI: 10.1016/j.dnarep.2015.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Preventing replication fork collapse to maintain genome integrity

Abstract: Billions of base pairs of DNA must be replicated trillions of times in a human lifetime. Complete and accurate replication once and only once per cell division cycle is essential to maintain genome integrity and prevent disease. Impediments to replication fork progression including difficult to replicate DNA sequences, conflicts with transcription, and DNA damage further add to the genome maintenance challenge. These obstacles frequently cause fork stalling, but only rarely cause a failure to complete replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
153
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(159 citation statements)
references
References 102 publications
1
153
1
1
Order By: Relevance
“…Supporting the central role of GOF p53-mediated transactivation of CHK1 in preventing collapse of replication forks, it was observed that a CHK1 inhibitor (Figure 2, G and H) or inhibition of CHK1 expression by transcriptional inactivation of GOF p53 leads to collapse of replication forks ( Figure 5G). It is known that the collapse of replication forks leads to either cell death or gross genomic rearrangement due to incomplete genome duplication (25,26). GOF p53-mediated fork stabilization, therefore, should allow the cells to evade these events detrimental to cell growth, although the cells enter S phase as early as p53-null cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Supporting the central role of GOF p53-mediated transactivation of CHK1 in preventing collapse of replication forks, it was observed that a CHK1 inhibitor (Figure 2, G and H) or inhibition of CHK1 expression by transcriptional inactivation of GOF p53 leads to collapse of replication forks ( Figure 5G). It is known that the collapse of replication forks leads to either cell death or gross genomic rearrangement due to incomplete genome duplication (25,26). GOF p53-mediated fork stabilization, therefore, should allow the cells to evade these events detrimental to cell growth, although the cells enter S phase as early as p53-null cells.…”
Section: Discussionmentioning
confidence: 99%
“…36,56), increase in cyclin A expression leads to firing of more origins of replication (Figure 1 and Supplemental Figure 9F), whereas increased CHK1 expression prevents their collapse (Figure 2), thus quickening genome duplication ( Figure 3) and proliferation of cells with genetic abnormalities, as evidenced by micronuclei formation (Figure 4 and Figure 5E). In contrast, due to their inability to upregulate cyclin A and CHK1 expression, p53-null cells or cells expressing GOF-deficient p53 mutants activate fewer origins than cells with GOF p53 (Figure 1) and face a vulnerability to collapse of replication forks (Figure 2), which is known to cause incomplete genome duplication, gross genome rearrangement, and cell death (25,26).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stalled forks need to be stabilized to prevent nuclease cleavage or degradation to maintain genome integrity (Cortez, 2015). In situations when there is no converging replication fork, the stalled fork must also restart to complete DNA synthesis.…”
Section: Smarcal1mentioning
confidence: 99%
“…Nonetheless, the wellrecognized sources of replication stress include unrepaired DNA lesions, mis-incorporated ribonucleotides, unique DNA sequences that are prone to form secondary structures (e.g., G-quadruplex or G4), collision of the replication fork with the transcriptional machinery, an RNA-DNA hybrid (or R-loop) that is formed between a nascent RNA and the adjacent displaced single-stranded DNA (ssDNA), common fragile sites (CFS), and tightly packed genomic regions, such as heterochromatin (2). Because of these constant challenges faced by the replisome, mammalian cells have developed elaborate and complex strategies to resolve the replication stress and ensure the successful completion of DNA replication (1)(2)(3)(4).…”
mentioning
confidence: 99%